Advancing CART therapy for acute myeloid leukemia: recent breakthroughs and strategies for future development - Pérez-Amill, Lorena; Bataller, Àlex; Delgado, Julio; Esteve, Jordi; Juan, Manel; Klein-González, Nela (Frontiers in Immunology, 2023)
Chimeric antigen receptor (CAR) T therapies are being developed for acute myeloid leukaemia (AML) on the basis of the results obtained for other haematological malignancies and the need of new treatments for relapsed and refractory AML. The biggest challenge of CART therapy for AML is to identify a specific target antigen, since antigens expressed in AML cells are usually shared with healthy haematopoietic stem cells (HSC). The concomitant expression of the target antigen on both tumour and HSC may lead to on-target/off-tumour toxicity. In this review, we guide researchers to design, develop, and translate to the clinic CART therapies for the treatment of AML. Specifically, we describe what issues have to be considered to design these therapies; what in vitro and in vivo assays can be used to prove their efficacy and safety; and what expertise and facilities are needed to treat and manage patients at the hospital.